2018
DOI: 10.1007/978-3-030-00662-4_27
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the QUB/e Method for Fast In Situ Measurements of the Thermal Performance of Building Fabrics in Cold Climates

Abstract: The QUB/e method is a dynamic measurement method developed to estimate the whole heat loss coefficient and local U -values of a building in a single night without occupancy. The ability of the method to provide reliable results was demonstrated experimentally in a climate chamber with controlled conditions in a previous work.This paper presents the findings from a series of in situ measurements carried out in a circa 1960s multi-family housing located in Stockholm area (Sweden). The U -values estimated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
3
8
0
Order By: Relevance
“…In order to obtain robust estimations, the heating time needs to be larger than 3 hours and the power larger than about 2000 W. The value of the heat transfer coefficient found by the QUB experiment is 𝐻 𝑄𝑈𝐵 = 61.2 W/K which can be compared with the initial supposed value 𝐻 𝑄𝑈𝐵 = 52.4 W/K obtained from the model used for the design of the experiment (equation ( 46)). The values of the heat transfer coefficient found by QUB experiment was compared with the value found by co-heating; as in other experiments, the differences between QUB and co-heating were about 5 -10 % (Mangematin, Pandraud, & Roux, 2012;Meulemans J. , 2018;Alzetto, Farmer, Fitton, Huges, & Swan, 2018;Alzetto, Pandraud, Fitton, & Heusler, 2018;Alzetto, Gossard, & Pandraud, 2014) The fact that small measurement errors can be obtained for relatively short heating duration can be explained by the time constants and the coefficients of the exponential response of the model given by equation ( 45) and shown in Figure 5d. For the model of the bungalow, the time constants can be grouped in five classes: a) Very short time constants (< 0.1 h) with significant coefficients in equation ( 45).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…In order to obtain robust estimations, the heating time needs to be larger than 3 hours and the power larger than about 2000 W. The value of the heat transfer coefficient found by the QUB experiment is 𝐻 𝑄𝑈𝐵 = 61.2 W/K which can be compared with the initial supposed value 𝐻 𝑄𝑈𝐵 = 52.4 W/K obtained from the model used for the design of the experiment (equation ( 46)). The values of the heat transfer coefficient found by QUB experiment was compared with the value found by co-heating; as in other experiments, the differences between QUB and co-heating were about 5 -10 % (Mangematin, Pandraud, & Roux, 2012;Meulemans J. , 2018;Alzetto, Farmer, Fitton, Huges, & Swan, 2018;Alzetto, Pandraud, Fitton, & Heusler, 2018;Alzetto, Gossard, & Pandraud, 2014) The fact that small measurement errors can be obtained for relatively short heating duration can be explained by the time constants and the coefficients of the exponential response of the model given by equation ( 45) and shown in Figure 5d. For the model of the bungalow, the time constants can be grouped in five classes: a) Very short time constants (< 0.1 h) with significant coefficients in equation ( 45).…”
mentioning
confidence: 76%
“…• on a house constructed inside an environmentally controlled chamber at University of Salford (Meulemans, Alzetto, Farmer, & Gorse, 2017;Alzetto, Pandraud, Fitton, & Heusler, 2018;Alzetto, Farmer, Fitton, Huges, & Swan, 2018); • on one of the twin houses of Fraunhofer Institute for Building Physics (Alzetto, Pandraud, Fitton, & Heusler, 2018); • on a house of 280 m 2 in southern France (Mangematin, Pandraud, & Roux, 2012); • on an apartment in a high-raise building in Stockholm (Meulemans J. , 2018).…”
Section: /26mentioning
confidence: 99%
“…the building tested and the weather conditions. Several studies have been previously reported on the performance of the method under actual climatic conditions in different regions of Europe [16,[21][22][23]. A concise description of the different tests and validation experiments is provided by Alzetto et al [24].…”
Section: Introductionmentioning
confidence: 99%
“…Bienvenido-Huertas et al recently published a comprehensive review [2] summarizing most of these methods. For the sake of completeness, let us add the QUB/e method [3] [4] to this review. However, these methods are not mature enough to be widely used by the community.…”
Section: Introductionmentioning
confidence: 99%